FILOGENI MOLEKULER ISOLAT BAKTERI F0-0-3-1 DARI MEDIA PEMELIHARAAN ROTIFER - Oktavianus Dalenoh; Stenly Wullur; Elvy L Ginting; Veibe Warouw; Detty N Rumampuk; Henneke Pangkey (Sam Ratulangi University, 2020)
The aim of this study was to construct molecular phylogeny of bacteria suspected to involve in decomposing the fishery waste as diet for rotifer culture. The bacteria were isolated from culture of rotifer and propagated for molecular analysis. Genomic DNA of the bacteria was extracted using DNeasy Blood and Tissue Kit (Qiagen). The 16S rRNA gene was amplified using primer pairs i.e. 8F (AGAGTTTGATCCTGGCTCAG) and 1492R (GGTTACCCT GTTACGACTT) and sequenced. The sequences were analyzed using Sequence Scanner and MEGA 7, and BLASTed on the NCBI website (www.ncbi.nml.nih.gov). Molecular phylogeny of the isolate was constructed using Neighbor Joining Tree method. Isolate bacteria F0-0-3-1 from culture of rotifer fed with fish waste diet was successfully propagated for molecular analysis. 16S rRNA gene of the isolate bacteria was successfully amplified and showed a DNA band at 1400 bp. Nucleotides sequence quality of the 16S rRNA gene i.,e QV+20 and CRL were 995 and 941 nucletides. BLAST result of the 16S rRNA gene showed 98.87% percent identity of the isolate bacteria F0- 0-3-1 with bacterial species in the genus Bacillus i.e. Bacillus weidmanni, Bacillus cereus dan Bacillus proteolyticus. Molecular phylogeny analysis showed that the three species was in the same clade.Keywords: Phylogeny, molecular, bacteria, rotifer, 16S rRNA geneÂ Penelitian ini bertujuan untuk mengkonstruksi filogeni molekuler bakteri yang diduga terlibat dalam proses penguraian limbah perikanan sebagai pakan untuk kultur rotifer. Isolat bakteri yang diperoleh dari kultur rotifer tersebut, dibiakkan dan DNA genomnya diekstrak menggunakan DNeasy Blood and Tissue Kit (Qiagen). Gen 16S rRNA isolat bakteri tersebut, diamplifikasi menggunakan primer 8F (AGAGTTTGATCCTGGCTCAG) dan 1492R (GGTTACCCT GTTACGACTT) selanjutnya, disekuens dan urutan nukleotida hasil sekuens dianalisis menggunakan program Sequence Scanner dan MEGA 7. Analisis homologi sekuens dilakukan dengan program BLAST nucleotide blast, pada situs NCBI (www.ncbi.nml.nih.gov) dan dilanjutkan dengan konstruksi filogeni molekuler menggunakan metode Neigbor Joining Tree. Isolat bakteri F0-0-3-1 berhasil disolasi dari kultur rotifer yang diberi pakan limbah ikan. Hasil amplifikasi Gen 16S rRNA isolat bakteri F0-0-3-1 terdeteksi dalam bentuk pita DNA pada posisi sekitar 1400 bp. Kualitas nukleotida gen 16S rRNA hasil sekuens menunjukan nilai QV 995 dan CRL 941. Hasil BLAST sekuens gen 16S rRNA isolat bakteri F0-0-3-1 pada database menunjukkan kemiripan 98% dengan spesies Bacillus wiedmanni. Hasil kontruksi filogeni menggunakan metode Neighbor Joining Tree menunjukan posisi isolat bakteri F0-0-3-1 berada pada clade yang sama dengan Bacillus weidmanni, Bacillus cereus dan Bacillus proteolyticus. Kata kunci: Filogeni, molekuler, bakteri, rotifer, Gen 16S rRNA